The regulatory region of MS2 phage RNA replicase cistron. IV. Functional activity of specific MS2 RNA fragments in formation of the 70 S initiation complex of protein biosynthesis. - Borisova, G P (1979)
The initiation region of the MS2 replicase cistron can be isolated as a fragment 59 bases in length protected from RNAase by the binding of the coat protein which serves as a translational repressor. This fragment MS2 R(-53 leads to 6) starts 53 bases before the initiation codon and retains full activity in binding ribosomes. We have investigated the functional activity in initiation of a series of fragments from this region variously shortened from the 5'-end. Ribosome protected fragments starting 17 or 21 bases before the AUG are unable to rebind to ribosomes. The shortest fragment which has this activity was produced by partial S1 nuclease digestion and starts 33 to 35 bases before the AUG. The initiation signal comprises some nucleotides between 21 and 33 bases before the initiation codon and the regulatory region responsible for initiation is longer than that protected by the ribosome in the final initiation complex.